Genes of pathogenicity of Enterococcus bacteria isolated from the vaginal biotope of women with chronic endometritis and reproductive disorders - E. A. Kungurtseva (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The microflora of the vagina plays an important role and should be regarded as a kind of ecological system that reacts to any changes in the state of the woman's body. Clinically expressed genital infections are etiologically associated with opportunistic microorganisms. In the pathogenesis of dysbiosis, an important role is played not only by quantitative and qualitative changes in microflora, but also by the "pathogenic potential" of microorganisms. The aim of the work was to reveal genes of pathogenicity in strains of Enterococci of the vaginal biotope of women of the studied groups. The study involved 102 women with reproductive disorders. The main group - women with chronic endometritis (CE), (n = 63), mean age - 31.0 ± 5.3. The diagnosis of chronic endometritis was made on the basis of morphological signs of histological examination of vacuum suction biopsy. The comparison group consisted of 39 women, representative by age; in this group the diagnosis was not confirmed by the results of the histological study of the endometrium. It has been established that enterococcal strains isolated only in women with reproductive disorders and chronic endometritis are a reservoir of genetic determinants of pathogenicity factors (efaA and asa1 (12.5 %) and sprE (37.5 %)).